Peran Liga Arab Pada Konflik di Timur Tengah dalam Perspektif Ekonomi-Politik Internasional - Alifian M. Nanda Pradana; Dina Yulianti (Jurnal ICMES, 2017)
The Arab League since its establishment in 1945 has failed to play a significant role in minimizing conflicts in the region. In some contemporary conflicts (Syria and Yemen), it is the the powerful countries of the League that became the main actors in the conflict. This raises the question, what is the reason behind this failure, especially political-economic reasons. Using the literature review, this paper finds that there are two factors contributing to the failure, namely economic interdependence between rich Arab countries and the United States, and secondly, a strong relationship between the United States and Israel. The later becomes the reason why the US takes advantage of its economic hegemony to defend the interests of Israel.